2018
DOI: 10.1111/tid.12924
|View full text |Cite
|
Sign up to set email alerts
|

The burden of sinus disease in cystic fibrosis lung transplant recipients

Abstract: Symptoms of SD affected more than 60% of CF LuTx recipients. Nasal endoscopic inspection identified alterations in 55%. The majority of patients presented the same isolates both on NL and BAL performed on the same visit. These results strongly support a role of paranasal sinuses as "reservoir" for descending re-colonization of the lung graft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 59 publications
1
7
0
2
Order By: Relevance
“…However, approximately 40% of lung transplant recipients in two studies reported intolerance to or lack of benefit with ELX/TEZ/IVA 20,22 . Sinus disease was noted as the most frequent indication for patients prescribed ELX/TEZ/IVA in the studies published by Ramos et al and Doligalski et al This finding aligns with the reported burden of sinus symptoms in approximately 60% of lung transplant recipients 22,25 . Improvement of sinus symptoms reported in the cases published by Benninger and Hayes provides yet another possible niche for modulator therapy in the lung transplant population 14,15 …”
Section: Discussionsupporting
confidence: 62%
“…However, approximately 40% of lung transplant recipients in two studies reported intolerance to or lack of benefit with ELX/TEZ/IVA 20,22 . Sinus disease was noted as the most frequent indication for patients prescribed ELX/TEZ/IVA in the studies published by Ramos et al and Doligalski et al This finding aligns with the reported burden of sinus symptoms in approximately 60% of lung transplant recipients 22,25 . Improvement of sinus symptoms reported in the cases published by Benninger and Hayes provides yet another possible niche for modulator therapy in the lung transplant population 14,15 …”
Section: Discussionsupporting
confidence: 62%
“…The nasal/paranasal sinuses have been proven to be a reservoir both in people with CF and primary ciliary dyskinesia. M orlacchi et al [ 20 ] demonstrated that a large number of patients had the same pathogens colonising both LAW and UAW after lung transplant. In addition, a number of studies have shown that P. aeruginosa and S. aureus clones can be found both in the LAW and UAW of these patients [ 12 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…These organisms may recolonize after transplantation and increase the risk of graft dysfunction. Although the evidence is insufficient, sinus surgery before transplantation can be considered, and even if surgery is not performed, accurate evaluation and treatment are required before and after transplantation [ 56 ].…”
Section: Disease-specific Guidelinesmentioning
confidence: 99%